Setizembrus Germann, a new genus of the subtribe Cotasteromimina with five new species from Malaysia (Coleoptera, Curculionidae: Molytinae, Pissodini) - Germann, Christoph (Zootaxa, 2025)
The genus Setizembrus Germann gen. nov., type species Setizembrus geiseri Germann sp. nov., is described here with five new species from Malaysia. It belongs to the subtribe Cotasteromimina (Pissodini, Molytinae). Setizembrus shares morphological similarities with the genera Obhylius Germann, 2021, Pseudohylobius Morimoto, 1962, Seticotasteromimus Germann, 2013 and Zembrus Germann & Grebennikov, 2020. All of the new species (Setizembrus semai Germann sp. nov., S. bispinosus Germann sp. nov., S. geiseri Germann sp. nov., S. lyali Germann sp. nov.. and S. pendleburyi Germann sp. nov.) were collected on mountain peaks or on a high-elevation plateau. The species are described, extensively photographed, and a diagnostic key to genera within Cotasteromimina and to all new species of Setizembrus is given.